EVALUASI SITUS WEB PARIWISATA WONDERFUL INDONESIA BERDASARKAN MODEL ICTRT (INFORMATION, COMMUNICATION, TRANSACTION, RELATIONSHIP, AND TECHNICAL-MERIT) - I Putu Sudhyana Mecha; Agung Suryawan Wiranatha; I Nyoman Sudiarta (JURNAL MASTER PARIWISATA, 2019)
Information technology, especially in industrial revolution 4.0 has changed the business practices of every sector, in which tourism is no exception. In Indonesia, the example can be found in case of tourism website Wonderful Indonesia. Given the important role of this website as a DMO (Destination Management Organization) website, then the evaluation was carried out in order to know its progress. This evaluation was based on ICTRT model that it consists of five dimensions, such as information, communication, transaction, relationship, and technical merit. There was 48 indicators on the ICTRT model, which can be divided as follows: information (18 indicators), communication (7 indicators), transaction (5 indicators), relationship (10 indicators), and technical-merit (8 indicators). Result of the Wonderful Indonesia website evaluation were obtained from a questionnaire distributed to 80 respondents, in which the sample came from travel agencies organization namely ASITA Bali. Based on evaluation result via IPA (Importance-Performance Analysis) graph, it showed that the indicators contained in Information, Transaction, and Relationship dimension needs to be considered, given the level of importance was high, but the performance was still low. Therefore, further development is required related to the indicators above, such as accommodation information, local weather information, attraction tickets, virtual tour, and privacy policy. Keywords: ICTRT model, tourism information, DMO website, Wonderful Indonesia